Normativity and Historicity of Imam Syafii's Rejection of Hisab in Determining the Beginning of the Hijri Month - Kusdiyana Kusdiyana; Badrun Taman; Mahkamah Mahdi (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2023)
This article examines Imam Syafi'i 's thoughts about determining the beginning of the Hijriyah month without using reckoning. The research method used is library research with a socio-political approach. Primary data is taken from the books by Imam Syafi'i and the scholars of the Shafi'i sect. Data were analyzed using interpretation, deductive-inductive, and historical continuity techniques. The findings of this study are that Imam Syafii determines the beginning of the Hijri month by sighting and the testimony of two fair people. If this is not fulfilled, Imam Syafii determines it with stigma, namely the fulfillment of the day in the month with 30 days. The factor of not using reckoning is due to the tendency of Imam Syafii as Nashir al-Hadith, so the meaning of Imam Syafii for " faqduru lah "is not oriented towards rationality with the science of reckoning which has a different meaning, compared to the meaning of al-hadith bi al-hadith as a form taking one hadith with another hadith that is considered closer in meaning. The socio-political conditions at that time also influenced because the rationalists had succeeded in getting closer to him; the government is currently intensively carrying out scientific reforms, and they are always spreading Inkar as-Sunnah teachings which can threaten the position of sunnah. So that the spirit in the development of science, including reckoning at that time, was more dominant in its rationality than the Syar'i element Artikel ini mengkaji pemikiran Imam Syafi’i tentang penentuan awal bulan Hijriyah yang tanpa menggunakan hisab. Metode penelitian yang digunakan adalah penelitian pustaka dengan pendekatan sosial-politik. Data Primer diambil dari kitab-kitab karya Imam Syafi’i dan para ulama mazhab Syafi’i. Data dianalisis dengan teknik interpretasi, deduktif-induktif, dan kesinambungan historis. Temuan penelitian ini adalah Imam Syafii menentukan awal bulan hijriah dengan rukyat dan kesaksian dua orang yang adil. Jika hal tersebut tidak terpenuhi maka Imam Syafii menetapkan dengan istikmal yakni penggenapan hari dalam bulan tersebut dengan 30 hari. Faktor tidak digunakannya hisab disebabkan kecenderungan Imam Syafii sebagai Nashir al-Hadis, sehingga pemaknaan Imam syafii terhadap “faqduru lah” tidak berorientasi pada rasionalitas dengan ilmu hisab yang memiliki makna lebih jauh, dibandingkan pemaknaan al-hadis bi al-hadis sebagai bentuk ta’kid satu hadis dengan hadis lainnya yang dinilai lebih dekat pemaknaannya. Kondisi sosial politik pada masa itu juga turut mempengaruhi, karena kaum rasionalis pada saat itu telah berhasil mendekat kepada pemerintah yang sedang gencar melakukan reformasi ilmu pengetahuan dan juga mereka senantiasa menyebarkan paham Inkar as-Sunnah yang bisa membuat kedudukan sunnah terancam. Sehingga ruh dalam perkembangan ilmu pengetahuan termasuk hisab pada saat itu lebih dominan rasionalitas nya dari pada unsur Syar’i nya